PERAN PENGADILAN NIAGA SEBAGAI LEMBAGA PENYELESAIAN PERKARA KEPAILITAN - Agustini Ari Dewi, Ni Putu; Yusa Darmadi, A. A. Ngr. (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 05, Juli 2013, 2013)
From the description above, we can know that the Commercial Court is different from the General Court, where a judge putusan can not be appealed. But in general the commercial courts and general courts alike. Commercial court is a specialized court. Where only certain cases are solved in the commercial court, such as the bankruptcy of a company.
Keywords: Commercial Court, Bankruptcy Settlement Agencies